Analisis Penggunaan Campur Kode Indonesia-Inggris pada Video Iklan Produk Kecantikan Lokal - Lira Mey Nisa; Tiodame Layupa Simanullang; Nabilah Siti Haniyah; Nijmal Adawiyah; Octavia Amelia; Tri Indah Prasasti (Departement of Mathematics Education, 2024)
This research aims to describe and explain the types and forms of Indonesian-English code mixing used in advertising videos. This study used descriptive qualitative method. The data used in this research are advertising videos on YouTube, especially advertising videos for local beauty products such as Make Over, Avoskin, Emina, Azarine, and Wardah. By watching videos advertising local beauty products on YouTube, researchers then analyzed the types and forms of code mixing used in advertisements. The research results show that the type of code mixing used in advertising videos for local beauty products is Outer Code Mixing. Of the total of 15 advertising videos that we analyzed, there were 50 uses of Indonesian-English code mixing. The forms of code mixing used are Intra sentential code mixing, Intra-lexical code mixing, and Involving a change of pronunciation.